Association between prognostic nutritional index and all-cause mortality among intestinal obstruction patients in the intensive care unit: a retrospective study - Ge, Yuanshuo; Wang, Zhe; Zhang, Cheng (Frontiers in Nutrition, 2025)
BackgroundIntestinal obstruction (IO) is a common surgical emergency associated with significant morbidity and mortality, particularly in critically ill ICU patients. The Prognostic Nutritional Index (PNI), calculated using serum albumin levels and total lymphocyte counts, has demonstrated prognostic value in various conditions. However, its role in critically ill IO patients remains unexplored.MethodsWe conducted a retrospective cohort study using the MIMIC-IV database. Critically ill patients with IO were identified, and their PNI values on the first day of ICU admission were recorded. Patients were stratified into quartiles based on PNI and analyzed for 30-day, 60-day, and 90-day all-cause mortality. Multivariable Cox regression models adjusted for potential confounders, and restricted cubic splines examined the relationship between PNI and mortality risk.ResultsA total of 701 patients were included in the analysis. Patients in the highest PNI quartile had significantly lower 30-day, 60-day, and 90-day all-cause mortality rates compared to those in the lowest quartile. After adjusting for covariates, higher PNI remained an independent predictor of reduced mortality (30-day HR 0.96, 95% CI: 0.93–0.98, p < 0.001; 60-day HR 0.96, 95% CI: 0.94–0.98, p < 0.001; 90-day HR 0.97, 95% CI: 0.95–0.99, p = 0.002).ConclusionPNI is independently associated with lower mortality in critically ill IO patients, supporting its utility as a risk stratification tool in this population. These findings underscore the importance of early nutritional assessment and intervention, and highlight PNI’s potential to guide clinical decision-making in the ICU setting.